Une nouvelle agglomération antique arverne : le site de « La Croix de la Pierre » (Beaulieu, Charbonnier-les-Mines — Puy-de-Dôme) - Bertrand Dousteyssier (Revue Archéologique du Centre de la France)
Thanks to aerial prospection, an ancient small town, as well as a segment from the Roman road Clermont-Ferrand – Augustonemetum / Saint-Paulien – Ruessio, were discovered near the towns of Beaulieu and Charbonnier-les-Mines (Puy-de-Dôme) in 2005. The results of this prospection, together with already-known bibliographical data and the study of several artefacts taken from private collections, enable us to provide a first spatial outline of the inside of the town (places of worship, funerary areas, housing). Although the site remains unexcavated, it is one of the best known towns of the civitas Arvernorum at the present time.